Ethnomathematics in bungkalang and sarakap crafts as mathematics learning media - Sari, Intan; Assidiqi, Hasby; Ranti, Mayang Gadih (International Journal of Insights for Mathematics Teaching, 2023)
Ethnomathematics is used to explore the presence of mathematics in cultural practices. Bungkalang and sarakap are Banjar crafts that are rarely studied and are starting to lose their existence in Banjar society. Educators also have not utilized this craft in learning mathematics. This study aims to determine the concept of mathematics in the bungkalang and sarakap, as well as the effects of these crafts as a medium for learning mathematics. The research approach is qualitative. The research was conducted in Tambak Baru Ilir involving 4 bungkalang and sarakap craftsmen, 1 Banjar culture administrator, 2 teachers, and 10 Banjar high school students. Data collection was completed using observation, interviews, documentation, and questionnaires. The data analysis was carried out using the interactive analysis model (Spradley model), and data validity was assessed using face validity and triangulation. The results showed that the mathematical concepts in the bungkalang and sarakap include counting activities and geometrical concepts (including circles and truncated cones). The use of bungkalang and sarakap as a medium for learning mathematics received good responses from teachers and students. Of the 12 informants, 11 of them were interested in trying to use the bungkalang and sarakap in learning mathematics.